STUDENTS’ CULTURAL INTEREST: AN OVERVIEW OF COMPUTER-BASED NATIONAL EXAMINATION (UNBK) 2019 - Rahdiani, Dian; Maulida, Nur Syifa; Nuraini, Nuraini (Pusat Asesmen dan Pembelajaran, 2019)
In the globalization era, it is very easy to get information about everything, including information about other countries’ culture, such as lifestyle, good and well-known school, joyful environment and complete facilities, beautiful places for a holiday, comfortable living places, as well as a various technological advances. Besides, there are many other cultural characteristics such as punctuality, independency, critical thinking, creativity, and more freedom in determining life and career paths. These situations make people more interested in learning about other countries’ cultures. The main objective of this study is to answer the following questions: how are students interested in learning about other countries' cultures? Could students’ interest of culture have positive contribution to their score in UNBK 2019? The sample of this study was 9th grader of junior high school who were taking the Computer-Based National Examination (UNBK) 2019 in 34 provinces and completed the questionnaires about their interest in learning other countries' cultures. This paper focuses on students’ cultural interests that assume a positive contribution to their academic performance. The analysis method used in this research is descriptive analysis and regression analysis. Results of the analysis, show that students who are interested in other countries' cultures have slightly higher UNBK scores compared to their peers. Therefore, based on the results analysis of this paper, cultural interest has made a positive contribution to the UNBK score in 2019. Further, researches recommend to give more attention to this variable in order to build students’ characteristics, and to enhance their academic achievement.